Moderasi Beragama Sebagai Pilar Kebhinekaan: Telaah Pemikiran Kh. Hasyim Asy'ari dan Kh. Ahmad Dahlan - Mohammad Dzaky Zaidan; Elisha Qotrunnada; Khansa Labiibah Hasna; Al bani Ridho Pratama; Abdul Fadhil (Jurnal Ilmu Pendidikan dan Sosial, 2025)
Religious moderation is an important pillar in Indonesia's diversity, because it functions as a bridge to embrace various differences and encourage tolerance between religious communities. In the context of diversity, religious figures have a central role in shaping the understanding and practice of moderation. This research aims to analyze the contributions and thoughts of K.H. Hasyim Asy'ari and K.H. Ahmad Dahlan regarding religious moderation, which is a pillar of diversity, and its relevance in religious life in Indonesia. Using a descriptive qualitative approach, this research analyzes the works and thoughts of the two figures through literature study and literature review. Data collection was carried out using a systematic analysis method to understand their thoughts and contributions in strengthening religious moderation in a multicultural society in Indonesia. It is hoped that this research can make a significant contribution to the development of the concept of religious moderation, not only in the context of religious life, but also in social interactions in various community groups in Indonesia, so that it can strengthen harmony and harmony in society in various aspects of daily life.